Perencanaan Strategis SI/TI pada Kesbangpol Prov.Sumsel - Dyon Fillipo; Dicky Pratama (PPPM Institut Teknologi Pagar Alam, 2025)
The rapid advancement of Information and Communication Technology has encouraged government institutions to implement Information Systems/Information Technology (IS/IT) that align with organizational objectives. Nevertheless, the current IS/IT utilization at the National Unity and Politics Agency (Kesbangpol) of South Sumatra Province remains constrained by system–business process misalignment, limited cross-departmental data integration, and the absence of a coherent IS/IT strategic plan. This study aims to formulate a comprehensive IS/IT strategic plan to guide the medium- and long-term development of Kesbangpol’s public services. The Ward and Peppard methodology was employed within a descriptive qualitative case-study design. Data were collected through field observations, reviews of the 2024–2028 Strategic Plan and standard operating procedures, interviews, and relevant literature. Internal business environment analysis used the Value Chain framework to identify organizational strengths and weaknesses, while external analysis applied PESTEL to map strategic opportunities and threats. These findings were synthesized through SWOT to derive SO, WO, ST, and WT strategic alternatives, which were subsequently translated into Critical Success Factors as prerequisites for effective implementation. Application development priorities were determined using the McFarlan Strategic Grid. The study recommends a prioritized IS/IT portfolio, including an Integrated Kesbangpol Information System, an Integrated and Verified Civil Society Organization Database, an Early Warning System for conflict and radicalism, a Digital Political Education Platform, and an internal Knowledge Management System. This strategic design is expected to enhance coordination effectiveness, improve data-driven service quality, and strengthen regional socio-political resilience in a sustainable manner